CHARACTERISTICS OF CLAYSTONES ACROSS THE TERRESTRIAL PERMIAN-TRIASSIC BOUNDARY: EVIDENCE FROM THE CHAHE SECTION, WESTERN GUIZHOU, SOUTH CHINA - Zhang S.; Peng Y.; Yu J.; Lei X.; Gao Y. (My University, 2006)
X-ray diffraction (XRD), scanning electronic microscopy (SEM) and X-ray fluorescence spectroscopy (XFS) studies were undertaken for claystones and/or mudstones from the Chahe section-a terrestrial Permian-Triassic boundary (TPTB) section. Our results indicate that the compositions of claystones in the Permian-Triassic boundary (PTB) interval (Beds 66f-68) outlined by biostratigraphy are different from claystones and/or mudstones found either below or above the interval of the same section. The clay minerals in the claystones of the PTB interval are mainly composed of illite-montmorillonite interlayers, with a few montmorillonites and chlorites. The other claystones and/or mudstones underlying and overlying the PTB consist of chlorites and/or kaolinites. Some authigenic clastic minerals, such as hexagonal dipyramid quartz and zircons, are only found in claystones in the PTB interval from the Chahe section and some marine PTB sections in western Guizhou and eastern Yunnan, southwestern China. In addition, some elements are present in abnormal concentrations in the claystones of the PTB interval as well. Most important is that we found no spherules in all the claystones studied, indicating no evidence of an extraterrestrial impact during the Permian-Triassic transition. The particular characteristics of the TPTB claystones at the Chahe section indicate their volcanic origin and thus provide a reliable auxiliary event marker for high-resolution demarcation of the TPTB in South China. They are also indicative in the marine PTB claystones in South China. Thus, the PTB claystones can be used as auxiliary markers for high-resolution correlation of the PTB from marine facies to land in South China when direct fossil evidence in the PTB sequence is lacking. © 2005 Elsevier Ltd. All rights reserved.
Keywords: CHAHE SECTION; CLAYSTONE; PERMIAN-TRIASSIC BOUNDARY (PTB); SCANNING ELECTRONIC MICROSCOPY (SEM); SOUTH CHINA; X-RAY DIFFRACTION (XRD); X-RAY FLUORESCENCE SPECTROSCOPY (XFS); Triassic; Permian; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian; Палеозой::Пермская